VwF A3-GPI modification of EPCs accelerates reendothelialization of injured vessels via collagen targeting in mice. (13th September 2016) - Tan, Hu; Song, Yaoming; Jin, Jun; Zhao, Xiaohui; Chen, Jianfei; Qing, Zhexue; Yu, Shiyong; Huang, Lan
Abstract: Despite the potential of endothelial progenitor cells (EPCs) to incorporate into sites of vessel injury and differentiate into endothelial cells, thereby contributing to the improvement of endothelial function, reendothelialization in some patients is insufficient for the prevention of abnormal endothelial growth because there is a lack of specific guided signals and low levels of congregation of the EPCs to the injured areas. If some type of molecular tool was able to guide EPCs specifically to the injured vessels, however, then the efficacy of cell implantation would improve. Here, we designed a strategy to modify these cells and improve their ability to directly target the injured vessels. As a homing molecule, we selected extracellular matrix components, such as collagen, which is exposed on catheter-injured arteries. To promote the adhesion of the EPCs to collagen, we painted the primary EPCs with a recombinant, glycosylphosphatidylinositol (GPI)-linked high-affinity ligand for collagen that is termed von Willebrand factor A3-GPI. These painted EPCs specifically bound to collagen in vitro and traveled to the damaged vessel in vivo . This novel strategy may allow for significant advancements in EPCs transplantation treatment.